Analytic survey of 57 cases of oral metastases. (30th January 2018) - Liu, Yingci; Vargo, Richard J.; Bilodeau, Elizabeth A.
Abstract : Background: Oral lesions have been reported among the first signs of an undiagnosed metastatic disease. Accurate diagnosis of an occult metastasis remains critical in determining the treatment course. Previous studies regarding oral metastatic tumors present varied data regarding the most frequent metastases to the oral cavity. These discrepancies echo the changes in incidence rates for certain malignancies over time and demonstrate the need for periodic updates in oral metastasis studies. Methods: Using Text Information Extraction System, a de‐identified pathology database, we compiled 57 cases over a period of 19 years using key terms to search for oral metastases. Results: For both males and females, the most common primary sites were lung (21.1%), liver (12.3%), breast (10.5%), kidney (10.5%), and colorectal (8.8%). We found an equal number of lung and breast metastases in females and metastases from the liver to be the most prevalent for males. In most of our cases (54.9%), the patient had no history of the primary malignancy and the oral lesion preceded awareness of the widespread cancer. Conclusions: As a departure from many previous case series, we found lung and breast metastases to be equally numerous in women and liver as the most common oral metastasis in men. Also, we identified a tendency for the patient to present with a previous history in certain malignancies, such as breast cancer, whereas in other malignancies, such as renal cell carcinoma, our data demonstrated a propensity to present in the oral cavity without history of a primary tumor.